Utilization, perception, and challenges of using social media in dental public health activities among public health dentists of India: a pilot study - Thakrar, Shifa; Parkar, Sujal (International Journal Of Community Medicine And Public Health, 2026)
Background: Social media has transformed public health dentistry by providing accessible tools to enhance community engagement and oral health outcomes. This study is aimed to assess utilization, perception and challenges of social media in dental public health activities among public health dentists of India. Methods: A cross-sectional pilot questionnaire survey was conducted in April, 2025. A self-designed, pre-tested 26-items questionnaire consisting of 10 close-ended questions for utilization, and 16 items based on Likert-scale (10 for perception and 6 for challenges). The questionnaire was formulated with Google Forms and distributed to public health dentists via email and personal online communication. Responses were noted in proportions. Results: Total 48 public health dentists have participated. The mean age was 39.69±6.89 years having male predominance (n=31, 64.58%). The 25 (52.08%) participants use social media for 1-2 hours daily. The 31 (64.58%) respondents believed that social media helps in spreading oral health awareness, and 35 (72.92%) supported its use for tobacco cessation. While, 38 (79.17%) advocated for government regulations to prevent misinformation. All participants acknowledged presence of inaccurate oral health content on social media. 32 (66.67%) participants agreed about ethical concerns of social media in dentistry and 28 (58.33%) refrained from using social media professionally due to fear of online trolling. Conclusions: While social media is increasingly recognized as a valuable tool in dental public health, its effective utilization is hindered by several challenges.